PERADABAN ISLAM PADA MASA PEMERINTAHAN KHALIFAH UTSMAN BIN AFFAN DAN ALI BIN ABI THALIB - Nafsiyah, Faizatun (As-Sulthan Journal of Education, 2025)
This article discusses the development of Islamic civilization during the reign of Caliph Uthman bin Affan and Ali bin Abi Talib, two important figures in the history of Khulafaur Rashidin. In its writing, this article is a type of library research with a descriptive-qualitative approach. Data was collected from various existing literature using content analysis. As for the result, during the time of Uthman bin Affan, the expansion of Islamic territory reached its peak, accompanied by the codification of the Qur'an as a monumental step in maintaining the authenticity of the revelation. His administration was also marked by the emergence of seeds of internal conflict due to the policy of appointing relatives as officials. Meanwhile, the reign of Ali bin Abi Talib was marked by various political and social challenges, including the occurrence of the Jamal and Shiffin Wars. Despite that, Ali remained committed to upholding justice and maintaining the unity of the people. This article examines the contribution of the two caliphs in forming the foundation of Islamic civilization in terms of politics, society, and religion, as well as their impact on the dynamics of the Muslim community in the future. Therefore, during the reign of both of them, they had a great influence on the development of institutions and values ​​in classical Islamic civilization.